Tension-Type Headache - Anurogo, Dito (Cermin Dunia Kedokteran, 2014)
Nyeri kepala tegang otot (tension-type headache -TTH) adalah nyeri kepala yang paling umum di seluruh dunia. Penulisan ilmiah ini bertujuan untuk mereview publikasi terkini yang terkait dengan TTH. Review ini berfokus pada pembahasan epidemiologi, etiopatofisiologi, potret klinis, pemeriksaan (fisik dan penunjang), penatalaksanaan, diagnosis banding, komorbiditas, pencegahan, dan prognosis.Tension-type headaches (TTH) are very common headache worldwide. The objective of this scientific paper was to review the recent and relevant publication about tension-type headache. This review focuses on epidemiology, etiopathophysiology, clinical portrait, physical examination and additional assessment, management, differential diagnosis, comorbidity, preventive, and prognosis in TTH.